Tomada de decisão : a racionalidade e a experiencialidade no design e projeto de produtos - Jardim Junior, Ery Clovis Petry (Universidade do Vale do Rio dos Sinos, 2018)
In different project subcultures, architects, engineers, and designers move between two paths to decide what are the next steps to be taken in product design and design: the path of reasoning and the path of intuition. These two paths are grounded in Epstein's theory (1999, 2003), called the CEST (Cognitive-Experiential Self-Theory of Personality). The path of reasoning or rationality is the path of decisions based on the logic of the methodologies, methods, tools and processes that the designer uses to advance the design as the information about design problems is structured. The path of intuition or experientiality is that of the decisions based on the experiences or personal experiences that the designer accumulated in heuristic processes, in which the methodologies, methods, tools and processes used to take a certain next step in the design are not clear enough, because all the information about the design problem is not available and it is necessary to 'fill in the gaps' to advance the design. These two paths, traced by architects, engineers and designers for the design and design of products, will be analyzed in this dissertation, based on studies of limited rationality (Simon, 1969, 1996) and limited intuition (Kahneman 2003) Rational- Experiential (Rational-Experiential - REI, Pacini and Epstein, 1999, 2003) as a research tool. The study was conducted online with 156 participants, revealing that in training analysis engineers tend to think more rationally and have more confidence in doing so, and, architects and designers tend to think in a more experiential way with more ability to think with feelings and intuition. In the analysis of experience time in product design and design the designers tend to think more rationally and have more ability and confidence to do so. In the analysis of the level of training, designers tend to think in a rational, experiential way and have more confidence and ability to act in this way.
Keywords: Racionalidade limitada; Experiencialidade; Racionalidade; Design de produto; Projeto de produto; Limited rationality; Experientiality; Rationality; Product design; Product design; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial